(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The current study included a group of (150) clinical swabs for patients suffering from burns, wounds, diabetic ulcers, and urinary tract infections for (69) males and (81) females, their ages ranging from 1- 68 years, for the period of November 2021 until March 2022, from Hospitals in Mosul. 75 samples of P. aeruginosa were isolated, representing (50%) of the total clinical samples, and the rate of isolation of them from samples of burns, wounds, diabetic foot ulcers, and urinary tract infections was 75% (42/56), 41.1% ( 23/56), 53.3% (8/15) and 8.7% (2/23), respectively. The antimicrobial susceptibility test was performed by the disk diffusion method, and it was found that the isolates are multi-antibiotic resistant. The percentage of resistance shown by the isolates was 70.7% for Piperacillin, 89.3% for Amikacin, 74.7% for Aztreonam and Levofloxacin, 81.3% for Gentamicin, Ceftazidime, and Cefepime, 76% for Ciprofloxacin, 80% for Netilmicin and Tobramycin, and 45.3% for Imipenem. The MIC values for the antibiotic Levofloxacin were determined using Macrodilution method, the results showed that the MIC value ranged between (0.5-512) μg/ml.The biofilm formation was assayed by the microtiter plate. Pyocyanin was extracted from the culture supernatants, and the absorbance values were measured using a spectrophotometer.The results showed that the antibiotic Levofloxacin at the MIC and Sub-MIC concentrations has an inhibitory effect to varying degrees on biofilm formation and pyocyanin pigment production.